Fetal Bovine Serum Substitute: Implication for Their Use in Translating Adipose-Derived Stem Cells from Bench to Bedside (Review) - Josh, Fonny; Mizuno, Hiroshi (Jurnal Plastik Rekonstruksi, 2012)
Recently, cell based therapy become a popular topic in research fields. This therapy offers great potential to treat many diseases. Adipose-derived stem cell (ASCs) is known to have the special characteristic due to its abundant availability and easily harvesting. Then it rapidly advanced into clinical trials for treatment of a broad range of medical conditions. Before translating ASCs from bench to bedside, this process is facing other problems through fetal bovine serum (FBS) elimination. Animal-derived serum is not a suitable option for ASCs expansion regarding the possibility of viral or bacterial infection and immune reaction. By replacing FBS with other non-animal serum which gives the same effect as FBS, may significantly enhances the safety and quality of ASCs. Pooled human AB serum (AB-HS), human serum (HS), pooled human plasma lysate (PL), umbilical cord serum (UCS)/placental serum (PS), thrombinactivated platelet rich plasma (tPRP) or serum free (SF)/xeno-free (XF) have been considered as FBS alternatives and some already applied in clinical trials with human cells. This article focuses on a prospective alternatives serum through the elimination of FBS.